Rapid Access to 10-(Cyclohexylimino)-7,9-diazaspiro[4.5]decane-6,8-dione Derivatives for HIV-1 Reverse Transcriptase Inhibition via Ruthenium-Catalyzed Ring-Closing Metathesis - Zhang, Tongbo; Wu, Shaotong; Cao, Yuanyuan; Fu, Yuhong; Guo, Ying; Zhang, Liang; Li, Li; Zhou, Han; Liu, Xiangyi; Li, Chao; Tang, Xiaowan; Zhang, Zhili; Tian, Chao; Wang, Xiaowei; Liu, Junyi (Synthesis, 2013)
HIV-1 reverse transcriptase, a multifunctional enzyme critical in the viral replication process, is an important target for suppression of virus spread. To date, there has been considerable effort to develop drugs against this enzyme with high activity and specificity, notably TNK-651 and its derivatives. In order to further improve the efficacy and to explore the structure–activity relationship, we have introduced the diazaspiro[4.5]decane-6,8-dione scaffold, with both a pyrimidine and an alicyclic ring, and have synthesized several new compounds in this class. Appreciable overall yield was achieved with minimized purification of the intermediates. Several compounds were tested against HIV-1 reverse transcriptase in vitro using nevirapine as a reference. One compound showed potent inhibitory activity, with an IC50 value (ca. 1.65 μM) comparable to that of nevirapine. Our synthetic method provides a rapid access to compounds in this class. Thus, many other similar compounds can be further studied in a timely and cost-effective manner.
Keywords: heterocycles; olefination; antiviral agents; HIV; ring closure; NNRTIs